Modeling of violence in a speech creativity photogrammetry Iraqi contemporary: أريج سعد عدنان الهنداوي (Al-Academy, 2016)
The latest events in Iraq and notably the fall of Mosul in the summer of 2014 have marked a turning point in The modern history of Iraq. Violent terrorist groups have overrun a vast area comprising of many towns in mid and northern Iraq causing many casualties and mass migration. Despite Iraq’s long history of pain and suffering the events of the second half of the year 2014 have been the most violent ever witnessed. From this point of view the researcher has tried to identify specifically in this time and place the effect these events have had on the Iraqi artist and to understand how the Iraqi artists depicted this violence in their works of art. The research comprises four parts; the first looked at the language used and the and procedural and substantive aspects, the second comprises of four studies the first of which presents a general look at local social values and their effect on the work of the artists, the second study identified the direct effect of the violence on Iraqi society, the third study looked into the direct effect of violence, terrorism and extremism on the Iraqi art movement. The fourth study looked at the theoretical framework this included ten indicators four of which were indicators from previous studies. The third part of the research is concerned with the methodology of the research, the social element and the cross sample chosen for the research and the reason this cross sample was -chosen. Six pieces of art were chosen and analyzed, five different artists created these six pieces, all six pieces were created after the events of the summer of 2014 and were inspired by these events. Represented the first sample (d. Balasim Muhammad) the people of Baghdad as a contemporary Iraqi art professors layer. (Motee Jumaili) city of Fallujah, which represents the artist professional practitioner. (Amal Fadel) represented the city of Ramadi & practitioner - not a professional artist layer. (Nibras Hashim) Mosul - represent young artist layer and upward. (Aqeel kharif) hobbyist layer & the reactions of Iraqi intellectual